“Impact of COVID-19 pandemic lockdown on early onset of puberty: experience of an Italian tertiary center” - Verzani, Martina (Ital J Pediatr, 2021)
At the end of 2019, an emerging atypical pneumonia called COVID-19 (coronavirus disease 2019), caused by the novel coronavirus defined as SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2), was first reported. COVID-19 rapidly expanded leading to an epidemic in China, followed by a global pandemic during the year 2020. In few weeks Italy was assaulted by a severe health emergency, constraining the Italian government to put in place extraordinary restrictive measures, such as school closures and a strict lockdown extended to the entire country at the beginning of March 2020. Since the beginning of lockdown, the Endocrinology Unit of Bambino Gesù Children’s Hospital has recorded a rapid increase of the outpatient consultations for suspected precocious or early puberty. We have now retrospectively analyzed all the consultations recorded in the database of our outpatient clinic from March to September 2020, and compared them with the consultations recorded in the same database from March to September 2019. Our preliminary data suggest a significant increase of precocious puberty cases in girls during the first period of COVID-19 pandemic. Further investigations in larger cohorts of children are needed in order to correlate the observed increase of precocious puberty with specific pathogenic factors.